Embracing Innovation: Teachers’ Adoption of Artificial Intelligence in Education - Ahmed, Jamil; Burdi, Asadullah; Abbasi, Faheem Ahmed (Journal of Development and Social Sciences, 2024)
This study aimed to investigate the adoption of contemporary popular artificial intelligence tools ChatGPT, Google Gemini, Meta AI, and others by educators in Pakistan. Although AI can significantly improve education through its competence in content creation, personalized education, and improved management, however, it is uncertain to what extent AI is adopted by educators. Based upon the descriptive survey design the study investigated how teachers are utilizing AI technologies for academic purposes. The study adopted a purposive sampling method targeting educators across schools, colleges, and universities actively engaged with AI tools. An online survey was designed to gather data from the respondents. Descriptive analysis was used to analyze the frequencies, purposes, and usage patterns of AI. The findings revealed that ChatGPT is the most popular choice for educators being used by all the respondents, and Meta AI and Gemini were also popular. The daily use of AI for educational purposes was common among educators. Based on the growing popularity of AI among educators, the study recommends policy reforms regarding curriculum development for AI literacy, organizing focused training programs to promote effective AI utilization targeting gender inclusion, and providing personalized technical support to users across different age groups.